1994
DOI: 10.1002/bjs.1800810146
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and inflammatory responses after open or laparoscopic cholecystectomy

Abstract: Metabolic and inflammatory responses and changes in fatigue were studied in groups of patients undergoing either laparoscopic (n = 14) or open (n = 10) elective cholecystectomy. The mean(s.e.m.) cortisol concentration was significantly (P < 0.001) increased from 342(80) and 424(91) nmol l-1 before operation to 895(46) and 966(53) nmol l-1 after surgery in patients undergoing laparoscopic and open cholecystectomy respectively. There was no difference in cortisol response between the groups. Glucose concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
85
0
7

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 25 publications
14
85
0
7
Order By: Relevance
“…In human medicine, many comparative studies between laparoscopic surgery and open surgery have been reported [10,15,18]. The increases in the serum interleukin-6 and C-reactive protein levels during laparoscopic surgery were found to be significantly smaller than those during open surgery [10,18]. These results demonstrate that aspects of the metabolic and acute-phase responses are attenuated following laparoscopic surgery, consistent with a reduction in tissue trauma [10].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In human medicine, many comparative studies between laparoscopic surgery and open surgery have been reported [10,15,18]. The increases in the serum interleukin-6 and C-reactive protein levels during laparoscopic surgery were found to be significantly smaller than those during open surgery [10,18]. These results demonstrate that aspects of the metabolic and acute-phase responses are attenuated following laparoscopic surgery, consistent with a reduction in tissue trauma [10].…”
mentioning
confidence: 67%
“…In the present cases, total skin incision length was only 6 cm, and three out of four incisions were only 1 cm. In human medicine, many comparative studies between laparoscopic surgery and open surgery have been reported [10,15,18]. The increases in the serum interleukin-6 and C-reactive protein levels during laparoscopic surgery were found to be significantly smaller than those during open surgery [10,18].…”
mentioning
confidence: 97%
“…It was observed that the increase in IL-6 after various surgical procedures is related to the severity of surgical trauma [23], while IL-6 production is decreased when surgery is undertaken using laparoscopic techniques [24]. Jakeways et al [25] demonstrated significantly less increase in mean IL-6 and C-reactive protein concentrations after laparoscopic compared with open cholecystectomy. Also, different types of surgery are associated with differences in cytokine secretion pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Hanly et al 19 proposed that CO 2 -mediated attenuation of the acute phase response may be the underlying mechanism of reduced systemic inflammatory response reported in earlier laparoscopic surgeries. [20][21][22] The immune-modulatory effect of CO 2 is apparently mediated by peritoneal acidosis as acidic solutions had the same effect. 23 Therefore, we speculate that abdominal CO 2 insufflation, rather than reduced tissue trauma, may account for underexpression of stress-response genes in LRP specimens compared with ORP specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients (n519) had urinary symptoms at the time of diagnosis. The median prostate-specific antigen (PSA) prior to surgery was 20.7 ng ml 21 . The clinical stages of all patients (n535) were at or above T2a.…”
Section: Clinical and Pathological Characteristicsmentioning
confidence: 99%